Long-term Effects of Adolescent Sport Concussion Across the Age Spectrum - Martini, Douglas N. (Am J Sports Med, 2017)
BACKGROUND: Research in sport concussion has grown precipitously over the previous decade due to increased scientific interest, as well as the media and political spotlight that has been cast on this injury. However, there is a dearth of literature regarding the long-term (>1 year post concussion) effects of adolescent concussion on cognitive and motor performance of high school athletes. PURPOSE: The purpose of this study was to evaluate the potential for long-term effects of concussion sustained during high school on cognitive and motor performance across the lifespan. STUDY DESIGN: Cross-sectional study. METHODS: Adults with (n=30) and without a concussion history (n=53) were recruited in younger (18–30 years old; n=43), middle aged (40–49 years; n=18), and older (60+ years; n=22) age groups. Each participant completed a computerized neurocognitive assessment and continuous tracking and discrete temporal auditory tasks with the hand and foot. Root mean squared error and timing variability were derived from the tracking and temporal auditory tasks, respectively. Data were analyzed by regression analyses for each recorded variable. RESULTS: There were significant age effects on neurocognitive task, continuous tracking task, and discrete auditory timing task performance (p’s < 0.05). There were no concussion history or interaction (concussion history by age) effects for performance on any task (p’s > 0.05). CONCLUSION: While longitudinal investigations are still needed, this cross-sectional study failed to identify any observable effect of adolescent concussion history on cognition or motor performance with age. CLINICAL RELEVANCE: There is a paucity of concussion history literature addressing the largest population of athletes participating in sport, the high school athlete. The results herein begin to address the possible effects of an adolescent concussion history on cognitive and motor performance across the age spectrum.